Risk management exploration of occupational safety and health for coconut tappers of Nira Satria Cooperative in Banyumas regency - Permatasari, Indah (Universitas Ahmad Dahlan, 2023)
Background: Occupational safety and health (K3) for informal sector is still low, as evidenced by the increasing trend of work accidents by 5-10%, including work accidents experienced by coconut tappers. Currently, there are only few research discussing about the implementation of SMK3, especially those dealing with risk management in reducing and preventing work accidents for coconut tappers. The objective is to explore the implementation of risk management for coconut tappers in working group of Nira Satria Cooperative, Banyumas Regency. Method: This qualitative research used a case study approach. It was conducted in two villages, namely Sokawera and Pageraji. There were ten research informants involved in this research consisting of the Chief of Pageraji and the Chief of Sokawera, the staff of community health center, the staff of Cooperative, the family of coconut tappers, and the coconut tappers of Nira Satria Cooperative. Data collection was carried out by in-depth interviews and field observations. Results: A total of 702 coconut tappers in Banyumas Regency were reported to have had accidents over the last five years. The work accidents experienced by coconut tappers of Nira Satria Cooperative were influenced by three factors, namely knowledge, availability of PPE, and behavior. The informants’ knowledge of risk management was very limited, five out of nine informants interviewed were still unable to identify and assess risk at work. The availability of PPEs is only 10% of the total tappers and when used they hindered the tappers’ time and work. The behavior of coconut tappers at work did not reflect good practice of risk management. Conclusion: Coconut tappers of Nira Satria Cooperative had not implemented risk management properly, there were no strict rules from the Cooperative and there was no support from the stakeholders. The coconut tappers and the stakeholders should have awareness to prioritize the safety and health of the coconut tappers in Banyumas Regency, especially those of Nira Satria Cooperative.